Ingestão plástica em aves marinhas necropsiadas pelo Projeto de Monitoramento de Praias da Bacia de Santos (PMP-BS) - Caetano, Pedro Baes (2022)
Plastic pollution is a problem that affects the world's oceans and is increasing over time, being recognized as a new environmental crisis. It is known that seabirds are an extremely threatened group of birds by many natural and anthropogenic threats, and they ingest plastic in a comprehensive way between species, suffering direct and indirect impacts. These species allow the assessment of plastic pollution in the open ocean. Monitoring approaches based on this have been implemented around the world, providing robust data to evaluate pollution over time and to inform policies to tackle plastic pollution. On the other hand, in Brazil, there is a delay in dealing with the issue, being considered one of the main polluters of the South Atlantic. From this, the present study used a database from the daily and uninterrupted monitoring of seabirds stranded on the South and the Southeast Brazilian coast and necropsy records by the Projeto de Monitoramento de Praias da Bacia de Santos (Beach Monitoring Program of Santos Basin, PMP-BS) to understand how the species that occur in Brazil are related to plastic pollution and being impacted along with other anthropic disturbances, to ultimately designate potential bioindicator species. A new diagnosis of marine species ingesting plastic is provided, with 8 new records (3 seabirds and 5 shorebirds). An increase in reports of plastic ingested by birds was identified between 2017 and 2020 and the main causes of death and anthropic impact (fishing, plastic ingestion, and oiling) and vulnerable species were diagnosed. Plastic is also seen to potentially influence causes of death related to starvation, a secondary effect of plastic ingestion when not a direct cause. From this, we discussed species of seabirds to be considered as bioindicators in Brazil.